Proses Ekstraksi Antioksidan dari Daun Kalanchoe pinnata: Studi Pengaruh Ukuran Partikel dan Kinetika Maserasi - Sabrianah Badaruddin; Alif Nur Laili Rachmah; Ratih C F Ratumanan; Ronald Darlly Hukubun; Tamaratritania Citta Trisnantari (Yayasan Literasi Sains Indonesia, 2025)
Kalanchoe pinnata leaves are rich in bioactive compounds, including flavonoids and phenolic constituents, which exhibit notable antioxidant properties. However, the efficiency of extraction processes is highly influenced by operational variables such as the type of physical pre-treatment and maceration duration. This study aims to evaluate the effect of three physical pre-treatment methods (manual grinding, chopping, and blending) and maceration periods ranging from 3 to 5 days on the antioxidant activity of K. pinnata leaf extracts using the DPPH radical scavenging assay. Results indicate that the grinding method combined with five days of maceration yields the highest antioxidant activity (95.04%), while blending leads to the lowest activity (81.78%), presumably due to heat-induced degradation of active compounds. Kinetic observations show that antioxidant activity tends to plateau on day five, particularly in ground samples. These findings highlight the critical influence of particle size reduction and solvent–solid contact time on mass transfer efficiency during extraction. This preliminary investigation provides a scientific basis for further research on the optimization of natural antioxidant extraction processes and the development of functional herbal formulations derived from K. pinnata leaves.